Use of traditional medicinal plants on sowek Island (Manggonswan village) Aruri Islands district, Supiori regency - Matheus Orboi; Ingrid Nortalia Kailola; Beatrix I S Wanma (Sean Institute, 2024)
Medicinal plants are types of plants that have medicinal functions and properties and are used to cure or prevent various diseases and have the meaning of containing active substances that can treat certain diseases. The research was carried out in Manggonswan Village from June to August 2022. The population in this study was 646 people with samples taken of 32 people. Data processing and analysis techniques use the SPSS method. The results of this research show that the types of medicinal plants used by the community in Manggonswan Village were identified as many as 22 species of plants which were used as ingredients for traditional medicine. There is Carica papaya, Annona muricata, Piper betle, Manihot esculenta, Jatropa curcas L, Coleus scutellarioides, Kalanchoe pinnata Syn, Vernonia amygdalina, Morinda citrifolia L, Sauropus androgynus, Orthosiphon aristatus, Annona aquamosa, Solanum torvum, Mimosa pudica, Peperomia pellucida, Averrhoa bilimbi, Psidium guajava, Cymbopogon citratus, Strobilanthes crispa, Pandanus amaryllifolius, Aloe vera, Graptophyllum pictum.The parts used are 4 parts of the plant which are used as traditional medicine ingredients, namely leaves by 25 respondents (78.1%), stems, roots, leaves. as many as 6 respondents (18.8%) and sap as many as 1 respondent (3.1%)